Implementing Digital Marketing to Increase the Income of MSMEs in Suka Aren Dalig Raya - Lenti Susanna Saragih; Aurora Elise Putriku; Sabda Dian Nurani Siahaan; Jufri Darma; Sri Wahyuni (Economic: Journal Economic and Business, 2025)
This research was conducted in Dalig Raya Village to improve the effectiveness of digital marketing for micro, small, and medium enterprises (MSMEs) in Suka Aren, Dalig Raya. The research used a 4D model. The Define stage was used to identify conventional marketing constraints that limit market reach. The Design stage included designing a digital marketing strategy through social media platforms like Facebook, Instagram, TikTok, and the Shopee e-commerce platform. The Develop stage involved creating visual content, collaborating with influencers, and utilizing interactive features. The Disseminate stage included content publication, sales monitoring, and evaluating the effectiveness of each platform. The results showed an average increase in revenue before and after digital marketing implementation of 43.04% within a three-month trial period. Shopee contributed the highest sales channel due to the integration of social media accounts with the business's e-commerce account. During the development process, TikTok was found to be the highest-performing social media platform with 14,200 content views, followed by Instagram with 2,502 viewers, and Facebook with 150 viewers. Facebook was effective in building communication and education, Instagram and TikTok excelled in increasing brand awareness, while Shopee served as the primary channel for sales conversion. Multi-channel strategies have been proven to increase brand awareness, drive sales, and have an impact on increasing the income of MSMEs.